ZAKAT SEBAGAI SOLUSI PEMBERDAYAAN EKONOMI LEMAH - Fitrianto; Furqonul Haq (Program Studi Ekonomi Syariah, 2023)
Zakat has an important role to drive the economy. The potential for Zakat Infaq and Alms (ZIS) in Indonesia in 2020 is very large (Rp. 327.6 T). However, it has only reached 3.9% of the total existing potential. BAZNAS is an institution that collects ZIS funds formed by the government from the central, provincial to district/city levels. BAZNAS Yogyakarta City has several zakat fund distribution programs, one of which is Jogja Sejahtera which aims to improve the economy for those who are less fortunate but have productive economic businesses. The research method uses literature study. The results of the study show that the BAZNAS of Yogyakarta City distributes zakat funds for productive economic empowerment to individuals and communities. BAZNAS Yogyakarta City also provides assistance to beneficiaries with the hope that the community will change from mustahiq to muzakki in the future